The government as marketer of innovation. Issue 5 (19th August 2014) - Lim, Jay Na
Abstract : Purpose: The Government's role in industrial innovation has always been conventionally viewed as a regulator rather than a marketer of industrial progress. By breaking out of the box, this study positioned the Government as a marketer of innovation and construction enterprises as "consumers" of innovation products. The marketing mix concept of 4Ps is applied in this study to tailor marketing strategies for Governments, who aim to stimulate a higher level of innovation performance in the construction industry. Design/methodology/approach: A survey of 97 construction enterprises in Germany is conducted to examine the innovation performance, strategies and resource utilisation of construction firms. Findings: The findings indicate that there is no one-size-fits-all national marketing strategy in promoting construction innovation. The Government is required to classify marketing strategies according to firm-sizes and enterprises' needs in relation to their national innovation environment to maximise their innovation potential. Practical implications: To illustrate this, marketing strategies according to firm-sizes for the Government to stimulate higher innovation performance of German construction enterprises are proposed. Originality/value: Acknowledging the role of Government as more than an enabler of construction innovation is required in today's knowledge economy. This study proposes that it may be time for Governments to review their conventional role and adopt a more proactive stance in promoting innovation in the manner that counts to construction enterprises.